Artificial selection, pre‐release diet, and gut symbiont inoculation effects on sterile male longevity for area‐wide fruit‐fly management. Issue 3 (21st November 2015) - Rull, Juan; Lasa, Rodrigo; Rodriguez, Christian; Ortega, Rafael; Velazquez, Olinda Elisabeth; Aluja, Martín
Abstract: Longevity is an important life‐history trait for successful and cost‐effective application of the sterile insect technique. Furthermore, it has been shown that females of some species – e.g., Anastrepha ludens (Loew) (Diptera: Tephritidae) – preferentially copulate with 'old', sexually experienced males, rather than younger and inexperienced males. Long‐lived sterile males may therefore have greater opportunity to find and mate with wild females than short‐lived males, and be more effective in inducing sterility into wild populations. We explored the feasibility of increasing sterile male lifespan through selection of long‐lived strains and provision of pre‐release diets with added protein, and inoculated with bacterial symbionts recovered from cultures of the gut of wild Anastrepha obliqua (Macquart). Artificial selection for long‐lived A. ludens resulted in a sharp drop of fecundity levels for F1 females. Nevertheless, the cross of long‐lived males with laboratory females produced a female F1 progeny with fecundity levels comparable to those of females in the established colony. However, the male progeny of long‐lived males*laboratory females did not survive in higher proportions than laboratory males. Provision of sugar to A. obliqua adults resulted in increased survival in comparison to adults provided only with water, whereas the addition of protein to sugar‐only diets had no additional effect on longevity. Non‐irradiated males lived longer than irradiated males, and supplying a generic probiotic diet produced no noticeable effect in restoring irradiated male longevity of A. obliqua . We discuss the need to evaluate the time to reach sexual maturity and survival under stress for long‐lived strains, and the inclusion of low amounts of protein and specific beneficial bacteria in pre‐release diets to increase sterile male performance and longevity in the field.